Study of the effect of external use of a brown algae product on the structural-functional continuum - B. Nasibullin; S. Gushcha; Yu. Dekhtyar; V. Volyanska (Kazimierz Wielki University, 2023)
The authors, in a study on 25 outbred Wistar white rats weighing 180-200 g, determined the effect of Lamidana (a product from sea brown algae) on the structural-functional continuum, that is, the correlation of the functional activity of the liver parenchyma and its structural characteristics. Methods. The detoxifying function of the liver was studied by the duration of sleep of animals due to the action of anesthesia - intraperitoneal administration of sodium thiopental (estimate the rate of metabolism of thiopental, carried out by the cytochrome-P-450-dependent monooxygenase system of hepatocytes). The structural and functional state of the liver parenchyma was assessed according to the study of histological preparations. The results of the studies showed that under the influence of the external application of "Lamidin" in the test rats, the liver1s detoxification function is enhanced (significantly significant decrease in the duration of sleep of animals). At the same time, structural signs of increased functional activity of hepatocytes are determined in the parenchyma. Conclusions. The authors believe that "Lamidan", due to the peculiarities of its chemical composition, enhances the metabolic and functional activity of hepatocytes but does not damage the correlative relationships between the structure and function of hepatocytes.